Acceptability and implementation potential of colorectal cancer screening and health literacy training: A qualitative study among general practitioners in deprived areas. - Géraldine Cazorla; Niamh M Redmond; Aurore Lamouroux; Alix Boirot; Michel Rotily; Maria Claudia Addamiano; Christian Balamou; Zineb Doukhi; Myriam Kaou; Françoise Couranjou; Cyrille Delpierre; Julien Mancini; et al. (PLoS ONE)
Background Colorectal cancer (CRC) is a significant contributor to cancer-related burden, ranking second in cancer mortality in France. Despite the proven survival benefits of systematic CRC screening, uptake remains suboptimal, particularly among people with limited health literacy (HL) and lower socioeconomic position. This study aimed to assess the acceptability of an e-learning training programme on HL and CRC screening among general practitioners (GPs) in deprived areas while also exploring strategies for its promotion and scale-up. Methods A qualitative study nested within the DECODE cluster-randomised controlled trial (NCT04631692) across four French regions was conducted. Semi-structured interviews (phone or online) were carried out to capture opinions, experiences, and recommendations of GPs in the intervention arm. Thematic analysis, employing manual and NVivo coding, was performed. Results The majority of 22 GPs (16/22) found the training acceptable, informative, tailored to their knowledge needs and offering great flexibility of use. The module on HL garnered more interest than the one on CRC screening, as it addressed a relatively new area for many GPs. It facilitated reflection on patient communication techniques and identified areas for improvement in physician-patient interaction. A perceived gap in the training was the insufficient interactivity in both didactic and virtual group sessions. Conclusion The findings of this study show high acceptability of the e-learning training by participants, indicating a potential for implementation, if kept concise, self-paced, asynchronous, and with a stronger focus on HL. The training helped GPs reflect on their practices, enhance HL knowledge, and improve patient communication strategies, leading some to adopt new techniques in daily interactions with low HL patients, beyond just screening.